(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The comelicaniid brachiopods, typical fossils of the Upper Permian, have been considered the markers for the Lower Dorashamian. They show a Wide geographical distribution, that is from the Southern Alps (Italy) to Himalayan region - Dolomites and Carnia (Italy), Central Slovenia (Yugoslavia), Bükk Mts. and Transdanubian Central Range (Hungary), Transcaucasia (USSR Armenia and North Iran) and Spiti (Himalayas, India). From stratigraphical researches carried out on the P/T boundary from the Southern Alps and Hungary, it has been found that the comelicaniid range is not restricted, as formerly supposed, to the Lower Dorashamian. The brachiopods span from Dzhulfian in the Bükk Mts., Lower Dorashamian in Transcaucasia, to a more likely Upper Dorashamian in the Southern Alps and Transdanubian Central Range. In these latter two localities a characteristic Comelicania assemblage (C. megalotis group and C. ladina group) occurs very close to the P/T boundary from sections in which the formational contact is considered transitional, both from lithological and paleontological points of view. The gen. Spitispirifer Waterhouse & Gupta, 1986 from the Spiti section is here considered a junior synonym of Comelicania Frech, 1901.